Virtual Cancer Care During the COVID-19 Pandemic in Alberta: Evidence From a Mixed Methods Evaluation and Key Learnings. Issue 9 (September 2021) - Watson, Linda; Qi, Siwei; Delure, Andrea; Link, Claire; Photitai, Eclair; Chmielewski, Lindsi; Hildebrand, April; Ruether, Dean; Rawson, Krista
Abstract : PURPOSE: This study reports on a mixed methods evaluation conducted within a provincial cancer program in Alberta, Canada. The purpose was to capture key learnings from a rapid virtual care implementation because of the COVID-19 pandemic and to understand the impact on patient and staff experiences. METHODS: Administrative data were collected for 21, 362 patients who had at least one virtual or in-person visit to any provincial cancer center from April 1, 2020, to June 10, 2020. Patient surveys were conducted with 397 randomly selected patients who had received a virtual visit. Surveys were also conducted with 396 Cancer Care Alberta staff. RESULTS: 14, 906 virtual visits took place in this period, and about 40% of weekly visits were virtual. Significant differences were observed in both patient-reported symptom questionnaire completion rates and referrals to supportive care services between patients seen in-person and virtually. Patients receiving active treatments reported significantly lower levels of satisfaction with virtual visits than those seen for follow-up, but overall 90% of patients indicated interest in receiving virtual care in the future. Staff thought virtual visits increased patients' access to care but less than one third (31.5%) felt confident meeting patients' emotional needs and having conversations about disease progression and/or end of life virtually. CONCLUSION: The COVID-19 pandemic has driven the rapid implementation of virtual visits for cancer care delivery in health care settings. The findings from this mixed methods evaluation provide a concrete set of considerations for organizations looking to develop a large-scale, enduring virtual care strategy.